Proteomic discovery of 21 proteins expressed in human plasma-derived but not platelet-derived microparticles - Smalley, David M.; Root, Karen E.; Cho, HyungJun; Ross, Mark M.; Ley, Klaus (Thrombosis and Haemostasis, 2007)
Microparticles (MPs) are small membrane vesicles generated by essentially all cell types. In the plasma, most MPs are derived from platelets, but those from other sources, particularly leukocytes (macrophages, lymphocytes, and neutrophils), endothelial cells, and even smooth muscle cells can be detected and appear to play an important role in normal physiology and various diseases. In previous work we analyzed the proteome of MPs generated from isolated platelets (platelet MPs). Here, we report on a comparative analysis of microparticles isolated from plasma (plasma MPs) versus platelet MP using two complementary methods of comparative analysis. The first method, spectral count analysis, yielded 21 proteins detected in plasma MPs (with a total spectral count of 10 or greater) that were essentially absent in platelet MPs (with a total spectral count of 1 or 0). An additional two proteins (von Willebrand Factor, albumin) were present in both types of MPs but enriched in the plasma MPs. The second method, isotope-coded affinity tag (ICAT) labeling of proteins, supported the spectral count results for the more abundant proteins and provided better relative quantitation of differentially expressed proteins. Proteins present only in the plasma MPs include several associated with apoptosis (CD5-like antigen, galectin 3 binding protein, several complement components), iron transport (transferrin, transferrin receptor, haptoglobin), immune response (complement components, immunoglobulin J and kappa chains), and the coagulation process (protein S, coagulation factor VIII).
Keywords: Secretion / exocytosis; platelet activation markers; vascular cell markers